Writing for Computer Science - Zobel, Justin (Springer London : Imprint: Springer, 2014)
All researchers need to write or speak about their work, and to have research  that is worth presenting. Based on the author's decades of experience as a researcher and advisor, this third edition provides detailed guidance on writing and presentations and a comprehensive introduction to research methods, the how-to of being a successful scientist. Topics include: ·         Development of ideas into research questions; ·         How to find, read, evaluate, and referee other research; ·         Design and evaluation of experiments, and appropriate use of statistics; ·         Ethics, the principles of science, and examples of science gone wrong. Much of the book is a step-by-step guide to effective communication, with advice on: ·         Writing style and editing; ·         Figures, graphs, and tables; ·         Mathematics and algorithms; ·         Literature reviews and referees' reports; ·         Structuring of arguments and results into papers and theses; ·         Writing of other professional documents; ·         Presentation of talks and posters. Written in an accessible style, and including handy checklists and exercises, Writing for Computer Science is not only an introduction to the doing and describing of research, but is a valuable reference for working scientists in the computing and mathematical sciences.